Single-nucleus transcriptomic mapping uncovers targets for traumatic brain injury - Yang, Qiuyun; Zhang, Lingxuan; Li, Manrui; Xu, Yang; Chen, Xiaogang; Yuan, Ruixuan; Ou, Xiaofeng; He, Min; Liao, Miao; Zhang, Lin; Dai, Hao; Lv, Meili; et al. (Genome Research, 2023)
The subventricular zone (SVZ) is a neurogenic niche that contributes to homeostasis and repair after brain injury. However, the effects of mild traumatic brain injury (mTBI) on the divergence of the regulatory DNA landscape within the SVZ and its link to functional alterations remain unexplored. In this study, we mapped the transcriptome atlas of murine SVZ and its responses to mTBI at the single-cell level. We observed cell-specific gene expression changes following mTBI and unveiled diverse cell-to-cell interaction networks that influence a wide array of cellular processes. Moreover, we report novel neurogenesis lineage trajectories and related key transcription factors, which we validate through loss-of-function experiments. Specifically, we validate the role of Tcf7l1, a cell cycle gene regulator, in promoting neural stem cell differentiation toward the neuronal lineage after mTBI, providing a potential target for regenerative medicine. Overall, our study profiles an SVZ transcriptome reference map, which underlies the differential cellular behavior in response to mTBI. The identified key genes and pathways that may ameliorate brain damage or facilitate neural repair serve as a comprehensive resource for drug discovery in the context of mTBI.
10.1101/gr.277881.123